When Time Is Not on Your Side: Delayed Recognition of Hand Compartment Syndrome After a Fracture - Edmund M. Bediako; Geraldine K. Mould; Eadbert Nortey; Abigail Mills-Annoh; Priscilla Kyei-Baffour; Ama Ekem; Jemima C. A. Clarke; Eugene F. E. K. Apaloo; Susan Quartey-Papafio; Kwame Ekremet (Case Reports in Orthopedics)
Compartment syndrome of the forearm is a well-described clinical entity, but only a few case reports on hand compartment syndromes have been reported due to its rarity. The early recognition and treatment of this potential threat to the limb are important in order to prevent permanent disability and other life-threatening complications. This is a documented case report on the late presentation of compartment syndrome of the hand following a fall.